Robust therapeutic effects on COVID-19 of novel small molecules: Alleviation of SARS-CoV-2 S protein induction of ACE2/TMPRSS2, NOX2/ROS, and MCP-1 - Youn, Ji Youn; Wang, Jian; Li, Qian; Huang, Kai; Cai, Hua (Frontiers in Cardiovascular Medicine, 2022)
While new variants of SARS-CoV-2 constantly emerge to prolong the pandemic of COVID-19, robust and safe therapeutics are in urgent need. During the previous and ongoing fight for the pandemic in China, Traditional Chinese Medicine (TCM) has proven to be markedly effective in treating COVID-19. Among active ingredients of TCM recipes, small molecules Quercetin, Glabridin, Gallic acid, and Chryseoriol have been predicted to target viral receptor ACE2 via system pharmacology/molecular docking/visualization analyses. Of note, endothelial dysfunction induced by oxidative stress and inflammation represents a critical mediator of acute respiratory distress syndrome (ARDS) and multi-organ injuries in patients with COVID-19 to result in mortality. Hence, in the present study, we examined whether these small molecules regulate viral receptors of ACE2 and TMPRSS2, redox modulator NADPH oxidase isoform 2 (NOX2) and inflammatory protein of monocyte chemoattractant protein-1 (MCP-1) in endothelial cells to mediate therapeutic protection against COVID-19. Indeed, these small molecules completely attenuated SARS-CoV-2 spike protein (S protein)-induced upregulation in ACE2 protein expression in endothelial cells. In addition, these small molecules abolished S protein upregulation of cleaved/active form of TMPRSS2, while native TMPRSS2 was not significantly regulated. Moreover, these small molecules completely abrogated S protein induced upregulation in NOX2 protein expression, which resulted in alleviated superoxide production, confirming their preventive efficacies against S protein induced oxidative stress in endothelial cells. In addition, treatment with these small molecules abolished S protein induction of MCP-1 expression. Collectively, our findings for the first time demonstrate that these novel small molecules may be used as novel and robust therapeutic options for the treatment of patients with COVID-19, via effective attenuation of S protein induction of endothelial oxidative stress and inflammation.